2018
DOI: 10.1101/314724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Proteomics Reveals Characteristic Proteins on Praziquantel-resistance inSchistosoma mansoni

Abstract: The extensive use of Praziquantel (PZQ), the only drug available to treat schistosomiasis, has brought concern about the emergence of PZQ-resistance/tolerance by Schistosoma spp., thus reaffirming an urge for the development of new treatment alternatives. Therefore, it is imperative and urgent to study this phenomenon trying to understand what is involved in its occurrence. Studies of Schistosoma spp. genome, transcriptome and proteome are crucial to better understand this situation. By stepwise drug pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Although the mechanism of action of PZQ and the molecular basis of juvenile resistance is not yet understood, previous studies have identified gene products that may play a role in both [18][19][20]39,40]. We have examined the differential regulation of a number of these genes previously and identified stress related genes that are differentially regulated in response to PZQ exposure in vitro [19] and in vivo [20].…”
Section: Expression Analysis Of Transcripts Related To Pzq-selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of action of PZQ and the molecular basis of juvenile resistance is not yet understood, previous studies have identified gene products that may play a role in both [18][19][20]39,40]. We have examined the differential regulation of a number of these genes previously and identified stress related genes that are differentially regulated in response to PZQ exposure in vitro [19] and in vivo [20].…”
Section: Expression Analysis Of Transcripts Related To Pzq-selectionmentioning
confidence: 99%
“…Pinto-Almeida et al [40] revealed proteins associated with S. mansoni PZQ resistance through comparative proteomics. PZQ resistance was generated in a fully susceptible isogenic S. mansoni strain treated with 0.3 μM PZQ and compared to a fully susceptible strain using high throughput LC-MS/MS identification of protein spots after 2-dimensional gel electrophosesis.…”
Section: Expression Analysis Of Transcripts Related To Pzq-selectionmentioning
confidence: 99%
“…Resistant isolates of Schistosoma spp. have been generated in the laboratory by several laboratories [88][89][90][91][92][93][94]. This is often achieved through the repeated, sub-lethal dosing with PZQ.…”
Section: Resistance To Pzq Could Arisementioning
confidence: 99%
“…There is no effective vaccine currently 3,9 . Other chemotherapy alternatives include oxamniquine and metrifonate, although these have some setbacks, such as being ineffective against all life stages of the parasite and severe side effects, which is why praziquantel is recommended [10][11][12][13][14][15][16][17] . Although praziquantel is effective, relatively safe and low cost, laboratory and field studies have shown the emergence of a resistant parasite strain in certain regions.…”
Section: Introductionmentioning
confidence: 99%